Information and Computer Literacy - Orel Šanko, Nena (Digital Transformation in Logistics and Supply Chain Management, 2026)
Today, information and computer security are extremely important for several reasons. Digitalisation has enabled a massive flow of data and information through computer networks, where information is often sensitive in nature, including financial data, personal identities, and business secrets. It is imperative to protect information from unauthorised access and misuse. In today's digital world, a lot of infrastructure is connected to computer networks, such as schools, hospitals, and transportation systems. Attacks on these systems can lead to significant financial or material damage and jeopardise people's lives. Hence, it is crucial to ensure systems’ security and resiliency against cyber-attacks, which have become increasingly common, sophisticated, and exploit vulnerabilities to steal data, spy, and cause harm. Thus, constant upgrading of security measures and raising awareness among people are essential. Therefore, information and computer security are of paramount importance for safeguarding privacy, economic stability, and national security in the modern digital world.